2020
DOI: 10.3906/vet-1905-67
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of aerobic bacteria isolated from honeybees (Apis mellifera) in Ordu Province

Abstract: of the honeybee and test their insecticidal effects on adult honeybees. 2. Materials and methods 2.1. Insect samples Samples of honeybees were collected from bee farms in the vicinity of Ordu,Turkey from May to September.The adult bees collected from the hives were placed in plastic boxes (20 × 20 cm) with punched lids for ventilation, and sugar cake was given in small pieces until the bees were transported to the laboratory for examination. Following this, healthy, diseased, and dead adult bees were separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Six papers did not deal with safety concerns. The paper of Bog et al (2020) described the results of an in vitro pathogenicity test of a B. licheniformis strain. The paper had methodological problems in relation to strain identification and used an unvalidated in vitro pathogenicity test with very high bacterial cell density.…”
Section: Gram-positive Spore-forming Bacteriamentioning
confidence: 99%
“…Six papers did not deal with safety concerns. The paper of Bog et al (2020) described the results of an in vitro pathogenicity test of a B. licheniformis strain. The paper had methodological problems in relation to strain identification and used an unvalidated in vitro pathogenicity test with very high bacterial cell density.…”
Section: Gram-positive Spore-forming Bacteriamentioning
confidence: 99%
“…Khan et al also reported that Bacillus is one of the most frequently isolated bacteria genus from the honey bee gut for Australian chalkbrood-inhibiting (Khan et al, 2020). Thus, It is not the first Bacillus report in the honey bee studies; previously, it was reported from different parts of the World (Wang et al, 2015;Audisio, 2017;Kačániová et al, 2020;Anjum et al, 2018;Boğ et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained bacterial isolates from dead A. mellifera caucasia L. adults by homogenisation. They were individually surface sterilised by using 70% ethanol for 3 min and washed three times with sterile water, according to Boğ et al (2020). The deceased honey bee bodies were homogenised in a feeder medium using a glass tissue mill, immersed in to the nutrient agar, and incubated at 30 °C for a week.…”
Section: Materıal and Methodsmentioning
confidence: 99%
“…Samples were collected from bee colonies using sterile scissors and protective clothes and then labelled by types of hives from respective sites. The collected samples were placed in plastic boxes or sterile tubes with punched lids and placed within small pieces containing sugar cake [ 31 ]. Then, samples were transported to the Microbiology Laboratory, College of Veterinary Medicine, Haramaya University, using an ice box.…”
Section: Methodsmentioning
confidence: 99%
“…The individual surface of live adult honey bees was sterilized by using 70% ethanol for 3 minutes and washing it 3 times with sterile water. The gut of honey bees was aseptically dissected by using a clipping stinger with sterile forceps and macerated with sterile scissors in 0.8% NaCl solution and kept at −4°C [ 31 ]. The samples were homogenized in 3 ml of peptone water and streaked on MacConkey agar, and incubated at 37°C for 24 hours.…”
Section: Methodsmentioning
confidence: 99%